Penser les crises futures de l’environnement urbain : le cas de l’espace portuaire de Tunis - Alexis Sierra; Cécile Cornou; Anouar Hechmi; Saloua Ferjani (Bulletin de l’Association de Géographes Français)
Tunis, as a national metropolis, can be approached as an environment, a largely artificial bio-physical-chemical milieu interacting with society. Due to the concentration of people, goods, activities and issues on a national scale, it constitutes a major risk environment, since the occurrence of a disruptive event, even of moderate intensity, has potentially catastrophic effects on different scales. Its port area, with its concentration of strategic infrastructures and the conditions of its site, is representative of this urban environment at risk, even if no disaster has yet struck it, unlike other Mediterranean port cities such as Beirut. This article looks at how to think about a future crisis in this type of environment.